Given P(A), P(B), and P(A n B) . Find the P(A' n B' | A')(adsbygoogle = window.adsbygoogle || []).push({});

We know P(AuB) = P(A)+P(B)- P(A n B)

Then

P(A' n B'|A') = P(A' n B' n A' ) / P(A') = P(A' n B') / P(A') = P(A u B)' /P(A') = [1-P(A u B) ]/ P(A') =

[1-P(A u B)] / [1-P(A)] Correct?

**Physics Forums | Science Articles, Homework Help, Discussion**

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Probability with conditionals

Tags:

Loading...

Similar Threads for Probability conditionals |
---|

I Equality in conditional probability |

I Rewriting of equality in conditional probability distribution |

B Conditional Probability, Independence, and Dependence |

I Conditional Expectation Value of Poisson Arrival in Fixed T |

**Physics Forums | Science Articles, Homework Help, Discussion**